2017
DOI: 10.1108/pmm-07-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

An altmetric analysis of ResearchGate profiles of physics researchers

Abstract: Purpose The purpose of this paper is to carry out an altmetric analysis of faculty members and research scholars of Department of Physics and Astrophysics, University of Delhi (India) (Univ.Delhi P&A) who are members of the academic social networking site ResearchGate. ReserachGate is a rich source of altmetric indictors such as publications, reads, profile views, citations, impact points, RGScore, followers and following, etc. The RGScore, unique to ResearchGate, was further explored in depth in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Meier and Tunger (2018) found that only 19% of ResearchGate users in physics, biology, medicine, and neuroscience had asked a question, and 49% had provided an answer. Shrivastava and Mahajan (2017) also found that only 12% of the physics researchers in an Indian university asked or answered a question. The evidence from these studies indicates that interactive functions are not well-used by science researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Meier and Tunger (2018) found that only 19% of ResearchGate users in physics, biology, medicine, and neuroscience had asked a question, and 49% had provided an answer. Shrivastava and Mahajan (2017) also found that only 12% of the physics researchers in an Indian university asked or answered a question. The evidence from these studies indicates that interactive functions are not well-used by science researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several studies have questioned which kind of activity is responsible for having a high RG score. In this regard, Shrivastava and Mahajan (2017) found that adding publications was the major activity that increases the RG score, whereas stated that the RG score is higher for highly cited authors and researchers who had published in reputed journals. However, Copiello and Bonifaci (2018) found that the main factor that influences the RG score is users' engagement instead of users' publications.…”
Section: Impact Assessment (Theme Ii)mentioning
confidence: 99%
“…(3) shift in libraries from buying individual journals to subscribing publishers' electronic databases; and (4) popularization of using academic social networking sites (ASNs) ( Hailu, Mammo, & Ketema, 2016;Nentwich & König, 2014;Shrivastava & Mahajan, 2017). With these changes, scholars and their institutions are expected to adjust themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Shrivastava and Mahajan (2017) provide a case study of a single department (the Department of Physics and Astrophysics at the University of Delhi). Of the departments' 173 members, 49 of members of the Department with ResearchGate profiles had no publication information associated with their profiles, while 94 had not uploaded any full-text documents (Shrivastava and Mahajan, 2017). It is not clear to what extent this reflects reluctance of the users to upload their publications, or simply the academic profile of the department (less senior members being less likely to have accrued a substantial publication record, for example).…”
Section: Relationship Of the Platforms To Open Access Publishingmentioning
confidence: 99%